Aplicación de Herramientas y Técnicas de Administración Financiera para la Empresa Comercial Multicon con Belleza Natural de la Ciudad de Loja, periodo 2012-2013 - Poma Sánchez, Manuela de Jesús (2016)
The work called "IMPLEMENTATION OF TOOLS AND FINANCIAL MANAGEMENT TECHNIQUES FOR COMMERCIAL COMPANY WITH NATURAL BEAUTY MULTICON Loja, PERIOD 2012-2013", aims to implement procedures for financial management and its financial statements by them to the manager owner make decisions that contribute to the progress and stability of the company, using it to make a proper management of the resources you have. To carry out the thesis was based on a general objective: Apply Tools and Techniques Financial Management for Business Enterprise "MULTICON" period 2012-2013, it would serve to determine whether the resources available to the company are producing profitability, liquidity and solvency and take advantage of market opportunities as flexibility and bargaining power with suppliers, threats such as increasing taxes, strengths to offer quality products at competitive prices and weaknesses as apply tools and technical financial administration risking financial management, to comply with the overall objective was necessary to implement four specific objectives. The first specific objective is to make vertical and horizontal analysis to determine the financial structure of the business and determine the increases and decreases of the items of the financial statements of the company, represented in current assets rose 42.17%, non-current assets 57.83% 25.85% current liabilities and assets with 74.15% so that you can show that the company has its own financing that allows you to carry out their activities in the future. The second specific objective is to: Apply financial ratios as indicators of liquidity, profitability, indebtedness and activity based on the financial statements of "MULTICON" of the years 2012-2013, to measure the liquidity of the company in this case has $ 1.22 in 2013, the activity was determined by means of inventory turnover which for 2013 has 3.36 times, compared to profitability was determined that the total return on equity provides 4, 22 cents and the total indebtedness of the company is 12% for 2013. The third specific objective is: Use the Statement of Sources and Uses, application of sources and uses disclosed that there was an increase in assets of $ 7,984.56 for 2013, while its accounts in assets also suffered reduction was aimed at addressing some of their obligations to suppliers, because their liabilities reduced. The fourth specific aim. Establish the equilibrium point to see if the total sales cover the costs and expenses and minimize risk and leverage resources, so it was observed that the company uses an installed capacity of 9.21% to reach sales of $ 47,965 37 so as to be able to maintain credibility and strength in the market. The fourth specific objective is to: Determine the projection of financial statements, revenues, costs, and expenses in order to enhance operational activities in the future and whether it will have an adequate financial structure and profitability forecast. 2014 the company obtained a net profit of $ 21,195.48 and $ 26,072.03 in 2015. At the end of the thesis the methodology to be applied to comply with it is defined within the method is scientific, deductive, inductive, analytic, synthetic, mathematical, and statistical research techniques such as observation was used, and interview the owner, eventually materials such as computer equipment, office supplies and library materials were used. It can be concluded that the company has a high percentage of costs that affect the profitability of it which does not allow you to get a level suitable liquidity to do so the company must purchase products in volume, look for new suppliers that give discounts for prompt payment as well as discounts on products so as to increase its liquidity and can have cash available to comply with their obligations.